Effects of Snow and Remineralization Processes on Nutrient Distributions in Multi‐Year Antarctic Landfast Sea Ice. Issue 7 (17th July 2022) - Sahashi, Reishi; Nomura, Daiki; Toyota, Takenobu; Tozawa, Manami; Ito, Masato; Wongpan, Pat; Ono, Kazuya; Simizu, Daisuke; Naoki, Kazuhiro; Nosaka, Yuichi; Tamura, Takeshi; Aoki, Shigeru; et al.
Abstract: We elucidated the effects of snow and remineralization processes on nutrient distributions in multi‐year landfast sea ice (fast ice) in Lützow‐Holm Bay, East Antarctica. Based on sea‐ice salinity, oxygen isotopic ratios, and thin section analyses, we found that the multi‐year fast ice grew upward due to the year‐by‐year accumulation of snow. Compared to ice of seawater origin, nutrient concentrations in shallow fast ice were low due to replacement by clean and fresh snow. In deeper ice of seawater origin (the lower half of the multi‐year fast ice column), remineralization was dominated by the degradation of organic matter. By comparison between first‐ and muti‐year ice, the biological uptake and the remineralization were dominated in relatively young ice and older ice, respectively, under the physical process of brine drainage. Plain Language Summary: Multi‐year landfast sea ice (fast ice) is abundant around the coast of Antarctica. Fast ice is an important component of Antarctic coastal marine ecosystems, providing a prolific habitat for ice algal communities. Although nutrients are essential for biological productivity within sea ice, the status of nutrients and processes affecting nutrient concentrations were previously not known for multi‐year fast ice. Here, we collected sea‐ice cores from multi‐year fast ice in Lützow‐Holm Bay, East Antarctica, and we analyzed nutrient concentrations using physical and biogeochemical parameters. Nutrient concentrations in the upper parts of the sea ice decreased due to the accumulation of clean (nutrient‐free) snow through melting and refreezing processes, contributing to upward ice growth. In deeper parts of the sea ice, nutrient concentrations were greatly affected by biological processes such as remineralization during the degradation of organic matter within sea ice. Key Points: Antarctic multi‐year landfast ice grew upward due to the year‐by‐year accumulation of snow Nutrient concentrations decreased in the upper sea ice due to the replacement by clean snow In deeper sea ice, remineralization by degradation of organic matter drove nutrient concentrations